Strategi Pemerintah Kabupaten Bengkalis Dalam Pencegahan Stunting di Kecamatan Mandau Kabupaten Bengkalis - Asiah Wasillah; Isril Isril; Desthy Nur A.I (Bahasa Indonesia, 2023)
This study aims to determine the village government's strategy in preventing cases of stunting risk. This research method is descriptive qualitative. The type of data used in this study is qualitative data, which is divided into primary data and secondary data. The village government's strategy in preventing cases of stunting risk is the focus of this research. Sources of data obtained from interviews and dokumentations. The results of this study indicate that the Mandau District OPD strategy in preventing stunting is good but not optimal, this is because there are still many people who do not understand stunting, and the community does not understand the right way to prevent stunting. The Government's strategy in preventing stunting is divided into three, the first is goal, the second is environment and the third is action.